PROFILING STUDENTS' READINESS FOR THE FUTURE: CLUSTER ANALYSIS OF 21ST-CENTURY COMPETENCIES AND CAREER INTERESTS AMONG SECONDARY STUDENTS - Norin Rahayu Shamsuddin; Fazillah Bosli; Siti Nur Alwani Salleh, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The growing emphasis on 21st-century competencies has highlighted the need to understand how these skills influence students' academic trajectories and career aspirations, particularly within Science, Technology, Engineering, and Mathematics (STEM) education. Despite the recognized importance of competencies such as leadership, collaboration, adaptability, and time management, limited research has explored how these self-perceived skills relate to students' future career interests. This study aims to investigate the relationship between secondary school students' self-assessed 21st-century competencies and their expressed STEM career preferences. A consensus clustering approach with q-fold cross-validation was applied to categorize students into meaningful groups based on their responses to self-assessment surveys measuring leadership, collaboration, adaptability, and career aspirations. The internal cluster validity indices (ICVs) and heatmap visualizations were used to determine the optimal number of clusters and to interpret differences in learning competencies and career interests. The results revealed two distinct student clusters. Cluster 1 exhibited high self-efficacy in leadership, collaboration, and organizational skills, coupled with focused career interests in physics, mathematics, and chemistry. In contrast, Cluster 2 displayed moderate confidence in 21st-century learning skills, particularly in leadership and time management, but showed a broader and more diverse interest in STEM careers, including environmental sciences, medicine, and veterinary sciences. These findings suggest that students with higher self-perceived competencies are more likely to pursue specialized STEM fields, while those with lower self-efficacy may require targeted interventions to enhance their leadership and organizational skills. This study has significant educational implications, emphasizing the need for tailored interventions that foster essential competencies, enhance STEM career motivation, and address disparities in career readiness. Future research should explore longitudinal effects of these profiles on students' academic and career trajectories.